THE STRATEGY OF SME / SMIS DEVELOPMENT IN DKI JAKARTA - Sri Mulyantini; Siti Hidayati; Marlina Marlina (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
This research aims to identify local government strategies in developing MSMEs. A qualitative method with observation techniques, in-depth interviews (depth interviews) and Focus Group Discussion (FGD) was applied to obtain primary data. The result was that IFE analysis with a score of 3.02 shows the internal conditions in a good category (the first rank was the marketing factor followed by production and information system factors). The result of the analysis of strengths, weaknesses, opportunities, and threats shows that the strategy lied in quadrant I. The right strategy in this quadrant is the aggressive strategy which in this case MSME players could take advantage of opportunities that are supported by internal strengths owned, oriented towards growth strategies. The total EFE matrix score is 3.15. which shows the external conditions are in a good category were in the first rank was the government's partisanship, the business world towards MSMEs, the separation of MSMEs and SMISs, and the availability of capital. The disadvantage is the high level of social and security vulnerability. Based on the QSPM and IFE Matrix, 2 cumulative alternative strategies were obtained with the TAS value of the Product Development Strategy of 2.54 and the TAS value of the Market Development Strategy of 2.78, as the main alternative that should be chosen. Based on QSPM and EFE, the TAS value of the Product Development strategy is 2.3 and the TAS value of the Market Development Strategy is 2.82, becoming the main alternative that should be chosen.